2008
DOI: 10.1111/j.1468-1293.2008.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral drug resistance among antiretroviral‐naïve persons with recent HIV infection in Thailand

Abstract: ObjectivesTo evaluate the prevalence and patterns of antiretroviral (ARV) drug resistance (ARV-DR) among ARV drug-naïve, recently infected persons with HIV in the 4-year interval (2003)(2004)(2005)(2006) after the inception of the National Access to ARV Programme for People who have AIDS in Thailand. MethodsCross-sectional study of patients with recent HIV infection for HIV risks, ARV-DR risks and baseline ARV-DR. ResultsSeven of the 305 patients (2%) had baseline ARV-DR. Via contract tracing, all seven patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 19 publications
2
25
3
Order By: Relevance
“…In this study, the prevalence of primary HIVDR in patients with recent infection was higher than that found in previous surveys of primary HIVDR in this region [8], [21], [22], [27]. However, the recent study in Thailand showed that primary resistance among men who have sex with men was approximately 7% [28].…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In this study, the prevalence of primary HIVDR in patients with recent infection was higher than that found in previous surveys of primary HIVDR in this region [8], [21], [22], [27]. However, the recent study in Thailand showed that primary resistance among men who have sex with men was approximately 7% [28].…”
Section: Discussioncontrasting
confidence: 62%
“…Previous reports of primary HIVDR among Asian patients ranged from 0% to 13.8% [8], [9], [21]–[24]. Results have varied by study methodology, route of HIV-1 transmission, duration of HIV-1 infection, HIV-1 subtype, pattern of local ART regimen use, and the reference list of RAMs used to assess the presence of relevant HIVDR mutations [4], [25], [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Population surveys [7][8][9][10][11][12] and mathematical models 20 to date have reported low levels of drug-resistant infections in African populations with increasing selective ARV drug pressure, but recent preliminary reports have suggested transmission of resistant strains directly after national ARV rollout programs. 21,22 The predominance of NNRTI-associated DRMs (mostly Y181C and K103N/S) in this baseline study probably results from the widespread use of NNRTIs as part of standard first-line ART and PMTCT regimens. Most solitary NNRTIassociated DRMs cause a complete loss of activity of efavirenz and nevirapine, 23 which may compromise the initial response to the standard first-line therapy.…”
Section: Discussionmentioning
confidence: 93%
“…Documented rates of transmitted drug resistance include 4% in 2003–2004 in Japan [7] and increases in Taiwan from 6.6% in 1999–2003 to 12.7% in 2003–2006 [8] and Thailand from <1% in 2003 to 5.2% in 2006 [9]. The vast majority of patients (∼80%) in Asia start treatment on AZT/d4T plus 3TC plus EFZ/NVP [10].…”
Section: Introductionmentioning
confidence: 99%